Nicotine-induced and D1-receptor-dependent dendritic remodeling in a subset of dorsolateral striatum medium spiny neurons. (25th July 2017) - Ehlinger, Daniel G.; Burke, Julian C.; McDonald, Craig G.; Smith, Robert F.; Bergstrom, Hadley C.
Graphical abstract: Highlights: Medium spiny neuron (MSN) dendrites are more complex in the DLS compared to DMS. Nicotine produced a lasting increase in the complexity of MSN dendrites in the DLS, but not DMS. The D1-antagonist SCH23390 blocked nicotine-induced neuroplasticity in the DLS. Nicotine selectively influenced the branching pattern of MSNs with more primary branches. Nicotine-induced neuroadaptations were selective for the distal portion of the dendritic tree. Abstract: Nicotine is one of the most addictive substances known, targeting multiple memory systems, including the ventral and dorsal striatum. One form of neuroplasticity commonly associated with nicotine is dendrite remodeling. Nicotine-induced dendritic remodeling of ventral striatal medium spiny neurons (MSNs) is well-documented. Whether MSN dendrites in the dorsal striatum undergo a similar pattern of nicotine-induced structural remodeling is unknown. A morphometric analysis of Golgi-stained MSNs in rat revealed a natural asymmetry in dendritic morphology across the mediolateral axis, with larger, more complex MSNs found in the dorsolateral striatum (DLS). Chronic nicotine produced a lasting (at least 21 day) expansion in the dendritic complexity of MSNs in the DLS, but not dorsomedial striatum (DMS). Given prior evidence that MSN subtypes can be distinguished based on dendritic morphology, MSNs were segregated into morphological subpopulations based on the number of primary dendrites. Analysis of these subpopulations revealed that DLS MSNs with more primary dendrites were selectively remodeled by chronic nicotine exposure and remodeling was specific to the distal-most portions of the dendritic arbor. Co-administration of the dopamine D1 receptor (D1R) antagonist SCH23390 completely reversed the selective effects of nicotine on DLS MSN dendrite morphology, supporting a causal role for dopamine signaling at D1 receptors in nicotine-induced dendrite restructuring. Considering the functional importance of the DLS in shaping and expressing habitual behavior, these data support a model in which nicotine induces persistent and selective changes in the circuit connectivity of the DLS that may promote and sustain addiction-related behavior.